2000
DOI: 10.1002/1098-2396(20001201)38:3<343::aid-syn14>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the histamine H2 receptor in monkey brain and its mRNA localization in monkey and human brain

Abstract: The distribution of histamine H2 receptor mRNA was determined by in situ hybridization histochemistry in human and monkey brain. In the case of monkey brain, we combined this technique with receptor ligand autoradiography to compare the distribution of mRNA and receptor binding sites. [125I]Iodoaminopotentidine ([125I]‐APT), a reversible, high specific activity antagonist with high affinity and selectivity for the H2 receptor, was used for receptor autoradiography. Radiolabeled oligonucleotides derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…The caudate putamen, ventral striatal complex, and amygdaloid nuclei (bed nucleus of the stria terminalis) are among the richest brain areas. The distribution of the mRNAs is generally in agreement with that of the corresponding binding sites [192,251,252]. In the striatum, the absence of mRNAs in the substantia nigra and the loss of binding sites in Huntington's disease [253] indicate that H 2 receptors are expressed by intrinsic neurons.…”
Section: Distributionsupporting
confidence: 60%
See 1 more Smart Citation
“…The caudate putamen, ventral striatal complex, and amygdaloid nuclei (bed nucleus of the stria terminalis) are among the richest brain areas. The distribution of the mRNAs is generally in agreement with that of the corresponding binding sites [192,251,252]. In the striatum, the absence of mRNAs in the substantia nigra and the loss of binding sites in Huntington's disease [253] indicate that H 2 receptors are expressed by intrinsic neurons.…”
Section: Distributionsupporting
confidence: 60%
“…Autoradiographic localization of the H 2 receptor using [ 125 I]iodoaminopotentidine in the guinea pig [211,251], monkey, and human brain [191,210,252] shows it distributed heterogeneously ( Fig. 9.2).…”
Section: Distributionmentioning
confidence: 99%
“…Autoradiographic mapping, immunohistochemical analysis and in situ hybridization data have also indicated the presence of histamine receptors in the cerebellum [10][11][12][13]. Interestingly, by using extracellular recordings on rat brain slices, we find that histamine excites cerebellar Purkinje cells, granule cells, and nuclear neurons [1,14], and improves motor performances mediated by the cerebellar interpositus nucleus (IN) or fastigial nucleus (FN) [14,15].…”
Section: Introductionmentioning
confidence: 75%
“…7b). A two-way ANOVA with repeated measures revealed a significant effect of time (F (3,135) =20.330, P<0.01), treatment (F (4,45) =6.668, P<0.01), and time×treatment interaction (F (12,135) =50.949, P<0.01). Newman-Keuls post hoc test indicated that microinjection of histamine (n=10) into the cerebellar IN significantly lengthened the endurance time of rats on the rotating rod 0 h (P<0.01, Fig.…”
Section: Blockage Of Hcn Channels In the Cerebellar In Attenuates Hismentioning
confidence: 96%
“…Immunohistochemical studies have offered convincing evidence that the histaminecontaining neurons project from the tuberomammillary nucleus to both cortex and nuclei of the cerebellum [4,5] . Autoradiographic mapping, immunohistochemical analysis and in situ hybridization experiments have indicated the presence of histamine H 1 , H 2 and H 3 receptors in rat cerebellar cortex and deep cerebellar nuclei [6][7][8][9][10][11][12] . All of these studies reveal the existence of the direct histaminergic pathway between hypothalamus and cerebellum [13] .…”
mentioning
confidence: 99%